Knowledge Sharing in Pakistani Universities and its Islamic Motives: An Empirical Study of Teachers’ Behaviours (Al-Qamar, 2021)
This study revolves around the conducts of university teachers and the responsibilities that Islam has posed upon them regarding knowledge sharing. Islam has given the responsibilities to scholars and teachers to spread the knowledge to the community. It is the religious obligation of teachers to convey the knowledge to the humanity for the sake of awareness and consciousness. The study empirically investigates the knowledge sharing behaviours of university teachers in Pakistani universities. It also investigates the ways and channels of communication that university teachers adopt for the sake of knowledge sharing. 1130 university teachers were the sample of this study. Tool of the study was a questionnaire having two parts; Likert scale questionnaire and open-ended questionnaire. Collected data were analyzed with the help of SPSS. Results show that Pakistani university teachers involve themselves in knowledge sharing activities to fulfill their religious obligation. They also have positive behaviour regrinding knowledge sharing activities.
Keywords: Knowledge sharing; University teachers; Islam